Social Media Optimization in School Image Transformation: Instagram Interactive Strategies in Schools - Ela Trisna Pratiwi; Abdul Wahid Zaini; Suhermanto (Al-Qalam Institute, 2023)
This research focuses on exploring the role of Instagram as a social media platform in building the school's image, with a case study on Public Senior High School 1 Paiton. In today's digital context, social media has become a strategic tool for educational institutions to strengthen their relationships with their communities and promote their values and achievements. This study uses a qualitative approach with a case study method, where data collection techniques include in-depth interviews, direct observations, and analysis of documentation from the school's Instagram account. The results of the study show that the consistent use of Instagram is able to increase public engagement, strengthen relationships with students and parents, and build a positive image of the school in the eyes of the community. Engaging visual content and the use of interactive features such as Instagram Live are key in creating effective two-way communication. The implication of this study is that schools can utilize Instagram not only as an information medium, but also as a strategic tool to shape the image of the institution and build public trust.